Comparative analysis of Fusarium graminearum infection in maize, wheat, and rice (JÓVENES EN LA CIENCIA, 2023)
Plants such as maize, wheat, and rice, belonging to the grass family, are of great economic importance as they are the basis of world nutrition. Therefore, it is out most important to study and report pathogens that put this group of plants at risk, because they cause diseases that result in decreased product quality and loss of commercial yield. Fusarium graminearum is a necrotrophic fungus that causes Fusarium head Blight in wheat and Cob rot in maize. In the present research we determined and compared the pathogenicity of hyper and hypo-virulent mutants with the wild-type strain of F. graminearum on maize, wheat, and rice. For this purpose, we employed techniques such as genomic DNA isolation, polymerase chain reaction (PCR), seed germination under greenhouse and laboratory conditions, inoculation of conidia in suspension in seedlings and seeds as well as the use of epifluorescence microscopy. Our results demonstrated first, the strains used in this study have the expected genotype; second, F. graminearum does not present an effect on seed germination; and third, F. graminearum can penetrate and grow in maize and wheat, but in rice results were inconclusive.